Soft finishing: A safe and comfort furnikids design for preschool children - Sumarno Sumarno; Ersnathan Budi Prasetyo (Universitas Ahmad Dahlan, 2021)
Furniture is inseparable from almost all human activities. It is used by individuals of all ages, both adults and children. However, the childhood period is a vulnerable period and hence requires protection. This study mainly aims to design safe, comfortable, fun, and aesthetic furniture for preschool children. This applied research aims to deliver a design through design concept, idea, and drawing stages. The concept was developed based on textual and visual data sources. The data were analyzed using interactive analysis techniques, including data reduction, data display, and data verification. The design process was carried out through the idea stage, alternative sketching stage, sketch selection stage, work drawing, and 3D drawings. The designed furnikids products include soft-furnished racks, tables, and chairs specifically designed for children. A Soft-finishing technique was applied to coat the product using foam and cloth to deliver a soft surface. The product was designed using various animal motifs, aiming to serve as media for introducing colors and animal shapes to children, in addition to serving as play equipment.